2021
DOI: 10.1111/beer.12346
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of CSR communication by hotels: The case of the Colombian Caribbean Region

Abstract: By measuring the level of CSR communication carried out by hotels located in the Colombian Caribbean region and identifying the main determinant factors influencing this level (including pressure from the different stakeholders), this paper contributes to deepening our understanding of the antecedents of CSR communication in small and medium-sized enterprises (SMEs) operating in emerging economies and, particularly, in the hotel industry, for which no previous studies on this topic could be uncovered. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Despite the growing body of literature about pandemics and crisis communication (including SCCT), the present literature review found a lack of research on anti-COVID-19 measures communicated through the corporate website. Moreover, previous research focuses on corporations including hotel chains ( Atasoy et al, 2022 ; Kwok et al, 2021 ; Wong et al, 2021 ) and high-class hotels ( Zizka et al, 2021 ), while neglecting independent and lower-classified hotels (including those on the coast) that do not have such managed/systematic communication ( Mohammed et al, 2016 ; Serra-Cantallops et al, 2021 ). This can put them at a disadvantage in a highly competitive international market with aggressive online promotion and PR/communication by the bigger players (international corporations), see Mohammed et al (2016) .…”
Section: Communicating Health-related Safety In Tourism and Hotel Ind...mentioning
confidence: 99%
“…Despite the growing body of literature about pandemics and crisis communication (including SCCT), the present literature review found a lack of research on anti-COVID-19 measures communicated through the corporate website. Moreover, previous research focuses on corporations including hotel chains ( Atasoy et al, 2022 ; Kwok et al, 2021 ; Wong et al, 2021 ) and high-class hotels ( Zizka et al, 2021 ), while neglecting independent and lower-classified hotels (including those on the coast) that do not have such managed/systematic communication ( Mohammed et al, 2016 ; Serra-Cantallops et al, 2021 ). This can put them at a disadvantage in a highly competitive international market with aggressive online promotion and PR/communication by the bigger players (international corporations), see Mohammed et al (2016) .…”
Section: Communicating Health-related Safety In Tourism and Hotel Ind...mentioning
confidence: 99%